Atomic force microscopy in process engineering : introduction to AFM for improved processes and products - Bowen, W. Richard; Hilal, Nidal (Butterworth-Heinemann/IChemE series., 2009)
Atomic force microscopy (AFM) is a surface imaging technique that can be applied at sub-nanometre resolution in liquids and gases. The same instrumentation can also be used to quantify directly the forces of interfacial interaction in such environments and is therefore a critical tool for process engineers and scientists, where AFM investigations are leading directly to improved processes and products. This is the first book to bring together both the basic theory and proven process engineering practice of AFM, and to present them in a way that is accessible and valuable to practising engineers, those who are improving their AFM skills and knowledge, and researchers who are developing new products and solutions using AFM. The book takes a rigorous but practical approach to ensure that it is also directly applicable to practical process engineering problems. Fundamentals of the techniques are concisely described and specific benefits for process engineering clearly defined and illustrated. Coverage of applications of AFM to important areas of process engineering is comprehensive. Each of the chapter authors are recognized authorities on their subject.